EXPERIMENTAL EVALUATION OF MOORVA AS A NON ABSORBABLE MONO FILAMENT SUTURE - Patil, *Nikhil; Vaidya, Umesh; Shriram Dawane, Jayshree (International Journal of Ayurveda and Pharma Research, 2016)
Suturing material plays a very important role in surgical procedures. The purpose of suturing (Seevankarma as called in the Ayurvedic terminology) is to approximate the wound edge for faster healing. This study was an attempt to assess Moorva mono filament fiber for the suturing purpose. An attempt to compare it with ethilon3-0 as non-absorbable suture in rats was done. Fully grown Moorva leaves were taken. Its fibers were separated under running water and subjected to autoclave. Moorva fiber tensile strength and thickness was measure before and after autoclave. Ethilon 3-0 tensile strength and thickness was measured. Rats were Anesthetized intramuscularly using 1ml syringe, after that suturing was done on prepared area. Redness, Discharge, Temperature, Approximation, Odema were observed for eight days and biopsy was taken on day eight. Temperature was measured on infrared thermometer. 12 rats were used for this study Trial group and control group skin closures were done on the same rat on different sites. Both the groups shows equivalent results for Redness, Odema, Discharge, Approximation, Temperature. Histopathological changes for inflammatory infiltrate, vascularity, fibrosis were same in both the groups. Moorva fibers tensile strength and thickness was less than ethilon 3-0 and this tensile strength and thickness was sufficient to hold the wound edges. The study proves that the Moorva fiber can be made and acceptable suturing material and it can be used for skin closures. Scope for further study Along term study on tissue absorbability property of Moorva fiber suturing material and detail chemical study of Moorva fiber.